INDEPENDENSI HAKIM DALAM MENJATUHKAN PEMIDANAAN PERKARA TINDAK PIDANA KORUPSI DIKAITKAN DENGAN PERMA NOMOR 1 TAHUN 2020 - Kevin Nikita Adi (2021)
This research discusses PERMA Number 1 of 2020 concerning Guidelines for Criminalization of Articles 2 and 3 of the Corruption Crime Law and the legal implications for the independence of judges in passing convictions. The purpose of this study is to analyze convictions by judges based on PERMA Number 1 of 2020 and to explain the legal implications of PERMA Number 1 of 2020 on the independence of judges in imposing punishment. The results of the research show that the criminal guidelines stipulated in PERMA Number1 of 2020 require judges to impose a sentence on the defendant to pay attention to the "category of state financial loss or the state economy, the level of error, impact and profit, the range of criminal charges, burdensome and mitigating circumstances, imposition of punishment, as well as other provisions relating to the imposition of a criminal." PERMA Number 1 of 2020 does not interfere with the independence of judges in imposing punishment because the criminal guidelines set out in it are not intended to interfere with or exert pressure on judges in judging, but rather provide guidance to judges in order to impose crimes in accordance with legal certainty, justice and proportional expediency.